2013
DOI: 10.5581/1516-8484.20130010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional evaluation of the joint status of hemophiliac adults at a Brazilian blood center

Abstract: BackgroundHemophilia is a potentially disabling condition as hemophilic arthropathy develops early in life and is progressive, especially in patients treated in an on-demand regime. ObjectiveThis study aimed to describe the structural joint status and the functional independence score of hemophiliac adults and correlate structural damage with the functional deficits found in these patients. MethodsHemophiliacs at the Juiz de Fora Regional Blood Center - HEMOMINAS Foundation, aged 18 years and over and treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
4
18
1
1
Order By: Relevance
“…Our data suggest that haemophilic joint damage starts at an early age and progresses until the age of 12-16 years, by which time aggregative damage approaches maximum but some further progression in arthropathy is possible. Several studies have reported a positive relationship between age and HJHS: a Lithuanian study (n = 20) showed higher HJHS in older children (mean score = 24.5) compared with younger (mean score = 11.6) [22]; a group from London showed a positive association of HJHS with age [23], and a cohort of 39 individuals with haemophilia from Brazil showed a significant positive correlation of Gilbert score with age [24]. Despite the fact that in each of these studies, the cohorts were either on prophylaxis or on-demand treatment, the joint health scores increased with age, however, the magnitude of increase was not as great as observed in our cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Our data suggest that haemophilic joint damage starts at an early age and progresses until the age of 12-16 years, by which time aggregative damage approaches maximum but some further progression in arthropathy is possible. Several studies have reported a positive relationship between age and HJHS: a Lithuanian study (n = 20) showed higher HJHS in older children (mean score = 24.5) compared with younger (mean score = 11.6) [22]; a group from London showed a positive association of HJHS with age [23], and a cohort of 39 individuals with haemophilia from Brazil showed a significant positive correlation of Gilbert score with age [24]. Despite the fact that in each of these studies, the cohorts were either on prophylaxis or on-demand treatment, the joint health scores increased with age, however, the magnitude of increase was not as great as observed in our cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing pain, muscle weakness and atrophy along with an increased risk of falling are key features of haemophilic arthropathy . Persons with mild haemophilia were excluded because they have no to very little haemophilic arthropathy . Various variables, known as fall risk factors in community‐dwelling older persons, were questioned with a standardized test battery in adult PWH.…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian Ministry of Health implemented a primary prophylaxis program in Brazil only at the end of 2011 because of the high cost of the coagulation factors. This program has benefited children aged 3 years or younger with severe haemophilia (or moderate haemophilia with coagulation factor VIII or IX levels below 2%) . Therefore, most adult patients with severe or moderate haemophilia A or B started the replacement of clotting factors late and developed severe sequelae due to repetitive bleeding, increased frequency of intra‐articular bleeding, with more risk of developing target joints (a joint in which recurrent bleeding has occurred four or more times in the past 6 months) and haemophilic arthropathy.…”
Section: Introductionmentioning
confidence: 99%